2012
DOI: 10.1063/1.3670742
|View full text |Cite
|
Sign up to set email alerts
|

Status of ion sources at National Institute of Radiological Sciences

Abstract: The National Institute of Radiological Sciences (NIRS) maintains various ion accelerators in order to study the effects of radiation of the human body and medical uses of radiation. Two electrostatic tandem accelerators and three cyclotrons delivered by commercial companies have offered various life science tools; these include proton-induced x-ray emission analysis (PIXE), micro beam irradiation, neutron exposure, and radioisotope tracers and probes. A duoplasmatron, a multicusp ion source, a penning ion sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…11 C-Met is a useful radiopharmaceutical to estimate the therapeutic efficiencies of radiotherapy such as conventional and particle radiotherapies [ 12 , 15 , 38 , 39 ]. Indeed, 11 C-Met has been used to estimate the therapeutic efficacy of carbon-ion radiotherapy at NIRS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 C-Met is a useful radiopharmaceutical to estimate the therapeutic efficiencies of radiotherapy such as conventional and particle radiotherapies [ 12 , 15 , 38 , 39 ]. Indeed, 11 C-Met has been used to estimate the therapeutic efficacy of carbon-ion radiotherapy at NIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, 14 C-MeAIB uptake by tumor tissues post 6-Gy irradiation did not change up to 5 days, while the uptake and accumulation of 14 C-MeAIB by tumor tissues irradiated with 25-Gy displayed significant decrease 3 days post-irradiation ( Fig 5 ). The short half-life tracer 11 C-Met has been used to estimate the therapeutic efficiencies of particle radiotherapy in clinical practice [ 12 , 15 ] and a decrease in the uptake of 11 C-Met has been shown to represent a positive treatment effect [ 45 ]. Thus, these results suggested that early changes in the uptake of 14 C-MeAIB may also have a potential to display an early effect of the carbon-ion beam dose and tumor responses to this radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 4•10 12 methane molecules can be produced each 20 minutes. To improve the efficiency of the ion source an electron string ion source is under development phase in collaboration with the Joint Institute for Nuclear Research (JINR), Russia (Hojo et al, 2008;Noda et al, 2011;Kitagawa et al, 2012). The proton irradiation generates a sufficient number of particles, however, the number of 11 C ions which are eventually injected into the HIMAC synchrotron is limited by the rather low efficiency of the compression/ionization process (Shirai et al, 2009), 10 7 -10 8 particles per injection versus the 10 10 usually necessary for treatment (Shirai et al, 2009).…”
Section: Radioactive Ion Beam Production Methodsmentioning
confidence: 99%
“…Other ion beam modalities have been investigated clinically in the past at LBL (neon, silicon and argon ions) and more have been suggested (oxygen and lithium ion beams) for future clinical practice. At the National Institute of Radiological Sciences (NIRS) in Japan, the HIMAC (Heavy Ion Medial Accelerator) can accelerate various ions (H, He, C, O, Ne, Ar, Fe, Kr, and Xe) in the therapeutic energy range. However, patients are treated only with carbon ion beams.…”
Section: Light Ionsmentioning
confidence: 99%